CQDs embed g-C3N4 photocatalyst in dye removal and hydrogen evolution: An insight review - Solayman, H. M.; Azrina, Abd Aziz; Noor Yahida, Yahya; Leong, Kah Hon; Sim, Lanching; Hossain, Md Kamal; Khan, Md Badiuzzaman; Zoh, Kyungduk (Elsevier Ltd, 2024)
Recent research has highlighted heterogeneous photocatalysts as a feasible contender for addressing energy shortages and environmental cleanup. One of the best semiconducting photocatalysts used in wastewater treatment, disinfection, and energy evolution is graphitic carbon nitrate (g-C3N4). Researchers have used carbon quantum dots (CQDs) to maximize and enhance the photocatalytic activity of g-C3N4 and to get over the material's limits due to photoinduced charges, partial surface area, and insufficient light-capturing difficulties. In this context, the fundamentals of CQDs and g-C3N4 are described in length, along with their structural state, synthesis, and modification techniques. The classification, manufacturing procedure, and characterization of CQDs/g-C3N4 are then highlighted in this paper. Following that, it is shown how CQDs/g-C3N4 photocatalysts are used in dye removal and hydrogen evolution studies. The discussion of CQDs/g-C3N4's present hurdles, unmet needs, and future research prospects concludes while keeping in mind their practical applications. This study shows that by embedding CQDs, the influence of charges, morphological modification, and textural quality of g-C3N4 have been altered. It is anticipated that this review will offer a practical overview and comprehension of CQDs embedded with g-C3N4 photocatalysts in order to promote their utilization. The ultimate goal of this review may be to impart a fundamental understanding of photocatalysis while also providing an expository evaluation of the most recent advancements in g-C3N4/CQDs photocatalysts in the sectors of energy and environmental security.